The Relationship Between Coach and Player Training Load Perceptions in Professional Soccer - Redkva, Paulo Eduardo [UNESP]; Gregorio da Silva, Sergio; Paes, Mauro Ricetti; Dos-Santos, Julio Wilson [UNESP] (SAGE Publications, 2017)
The training load imposed and perceived by coaches and soccer players, respectively, was compared for three weeks of the basic preparatory period of a professional soccer team through session ratings of perceived exertion (S-RPE). Participants were 24 professional Brazilian soccer players (all males, age: 24.1 ± 3.4 years) and their coaches. Athletes responded to the scale of perceived exertion (scores from 0 to10) after the training, while the coaches completed the scale prior to the training session, based on prior planning. The t-test for independent samples was used to compare S-RPE responses, and the Pearson correlation test was used to examine possible correlations between the parameters analyzed. There were no statistical differences between perceptions of prescribed (coaches) and experienced (players) S-RPE, and moderate correlations were found between these parameters (r =.60; p =.003). No statistically significant group differences were found in the perceived exertion during any of three types of training: physical, technical, or tactical. The results suggest that the S-RPE prescribed during the preseason period (by coaches) was not different from that perceived by professional soccer players.
Keywords: professional soccer; session ratings of perceived exertion; training load